Mathematics I - Walet, Niels (The University of Hull)
A first course in Mathematics for Physics students. Contains lecture notes, examples, ... as well as the files used to create these resources. Discusses: 1-Vectors in 2-space and 3-space; 2-Differentiation; 3- Integration; 4- Applications of Integration and 5- Differential Equations.